Enhancing Cognitive Learning Outcomes through HOTS-Based Learning in Indonesian Language Education: A Study of Grade VIII Students at SMPN 8 Sampang - Yayak Kurniawan; Jatim Desiyanto; Siti Nur Aisiyah (Indonesian Journal of Teaching and Learning (INTEL), 2025)
Purpose – This study aims to analyse the implementation of HOTS-based learning and its impact on improving cognitive learning outcomes in Indonesian language subjects for eighth-grade students at SMP Negeri 8 Sampang. The study is motivated by the low cognitive achievement of students, which is primarily influenced by conventional learning approaches centred on memorisation, despite the Merdeka Curriculum's emphasis on Higher Order Thinking Skills (HOTS). Methodology – The research uses the Classroom Action Research (CAR) model by Kemmis and McTaggart, conducted over two cycles. The sample consists of 32 eighth-grade students. Data were collected using cognitive learning achievement tests, observation sheets, and field notes. Quantitative data were analysed through average score calculations and completion rates, while qualitative data were analysed descriptively to complement the results. Findings – The study found a significant improvement in students' cognitive achievement. The average score increased from 62.50 in the pre-test to 80.31 in cycle II, and the mastery percentage rose from 31.25% to 87.50%. These results demonstrate that HOTS-based learning strategies effectively enhance cognitive outcomes and foster critical, analytical, and creative thinking skills. Novelty – The research contributes original insights into the effectiveness of HOTS-based learning in the context of Indonesian language education, particularly in junior high school settings. Significance – This study is beneficial for educators, curriculum developers, and policymakers seeking to improve cognitive learning outcomes by incorporating HOTS in educational strategies.